Analisis Pengaruh Kualitas Produk , Harga , dan Lingkungan Fisik Perusahaan Kue Lapis Legit XYZ Terhadap Kepuasan Konsumen Dalam Membangun Word of Mouth Positif - Lonardo Lonardo; Yasintha Soelasih (Jurnal Manajemen, 2014)
This research aims to analyze the effect of Product Quality, Price, and The Physical Environment on Customer Satisfaction and Positive World of Mouth. The sampling technique used in this study is convenience sampling, and the questionnaire was administered to consumers who have purchased the product. By analyzing the result of this research, it can be concluded that there are influences of Product Quality and Price on Consumer Satisfaction but there is no infleunce of the Physical Environment in the store on Customer Satisfaction. Product quality, Price and Physical Environment simultaneously influence the Customer Satisfaction to create Positive Word of Mouth.